PERKEMBANGAN BISNIS PARIWISATA SECARA PERSPEKTIF DI DANAU TOBA KOTA PARAPAT (Studi Kasus Danau Toba di Kecamatan Girsang Sipangan Bolon) - Bertha Meyke Waty Hutajulu; Rizki Ridwan; Reko Syarif Hidayatullah (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
This study aims to determine the development of the tourism business in the Lake Toba area, Parapat City, Girsang Sipanganbolon District in terms of the development perspective of Lake Toba as "International class Tourism". The type of research used is descriptive with a qualitative approach. Data collection was carried out using observation techniques, interviews and documentation. The results of the study show that the development of Lake Toba as a tourism business in Parapat City has experienced an increase such as in the MSME, Hospitality and Restaurant sectors. In developing the tourism potential of Lake Toba, Parapat City has strengths, weaknesses, opportunities and challenges. Its biggest strength is natural tourism, artificial tourism, and also cultural tourism. Weaknesses are human resources, facilities and infrastructure that still need to be improved, and limited capital. For this reason, it is necessary to have good cooperation between the central government, local government and the local community so that the development of the tourism business in Parapat City can be improved even better